Simultaneous separation and determination of six arsenic species in Shiitake (Lentinus edodes) mushrooms: Method development and applications. (1st October 2018) - Chen, Shuangyang; Yuan, Biao; Xu, Jiajia; Chen, Guitang; Hu, Qiuhui; Zhao, Liyan
Highlights: A method was established for simultaneous separation of 6 As species. Ultrasound-assisted extraction-anion exchange chromatography coupled with ICP-MS. Method was successfully applied to fresh Lentinus edodes and processed products. The HRI results indicated no particular risk for As species in L. edodes . A valuable guide of the toxicological risk of As in mushrooms for Chinese consumers. Abstract: A method for simultaneously separating six arsenic (As) species was established by ultrasound-assisted extraction-anion exchange chromatography coupled with inductively coupled plasma mass spectrometry. Six As species could be well separated within 15 min when 0.3 M acetic acid and 25 mM NH4 H2 PO4 were used as the extraction solvent and mobile phase, respectively. Under optimized conditions, the limits of detection and recovery of As species and the relative standard deviation were in the ranges of 0.31–0.59 μg/L, 94.30–102.75%, and 1.63–3.72%, respectively. Furthermore, the established method was successfully applied to fresh Shiitake ( Lentinus edodes ) mushrooms and processed products. The inorganic As contents of all samples ranged from 0.204 to 0.500 mg/kg, half of samples (>0.400 mg/kg) were close to the maximum contaminant level allowed by the Chinese (0.5 mg/kg). The health risk index estimation results indicated that no particular risk of As exposure to Chinese consumers existed in L. edodes .